2009
DOI: 10.1177/0890334408328295
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Buprenorphine Into Breast Milk and Calculation of Infant Drug Dose

Abstract: Little is known about the safety of buprenorphine (BUP) in breastfeeding. The aim of this work was to investigate the transfer of buprenorphine and its main active metabolite, norbuprenorphine (n-BUP), into human milk and to determine the drug dose and effects in exposed infants. Seven lactating women, who were maintained on BUP treatment because of previous opiate addiction, were studied in an open observational study. All mothers had a strong wish to breastfeed their newborn infants. Buprenorphine samples fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 23 publications
3
44
0
1
Order By: Relevance
“…27 These recommendations seem to be supported by the results of a small study of 7 breastfeeding women maintained on buprenorphine, which showed that the relative dose per kilogram of body weight in the infant was Ͻ1% of the dose per body weight of the mother. 28 Similarly, the range of nor-buprenorphine (a metabolite of buprenorphine) in the mothers' urine ranged from 175 to 933 nmol/L compared with 1 to 4.8 nmol/L in the infants. 28 The infants in this case series were at least if not more likely to be breastfed (70% at hospital discharge and 50% at 6-to 8-week follow-up visit) than those in previous studies (50%, 45%, and 21% as measured during hospitalization).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 These recommendations seem to be supported by the results of a small study of 7 breastfeeding women maintained on buprenorphine, which showed that the relative dose per kilogram of body weight in the infant was Ͻ1% of the dose per body weight of the mother. 28 Similarly, the range of nor-buprenorphine (a metabolite of buprenorphine) in the mothers' urine ranged from 175 to 933 nmol/L compared with 1 to 4.8 nmol/L in the infants. 28 The infants in this case series were at least if not more likely to be breastfed (70% at hospital discharge and 50% at 6-to 8-week follow-up visit) than those in previous studies (50%, 45%, and 21% as measured during hospitalization).…”
Section: Discussionmentioning
confidence: 99%
“…28 Similarly, the range of nor-buprenorphine (a metabolite of buprenorphine) in the mothers' urine ranged from 175 to 933 nmol/L compared with 1 to 4.8 nmol/L in the infants. 28 The infants in this case series were at least if not more likely to be breastfed (70% at hospital discharge and 50% at 6-to 8-week follow-up visit) than those in previous studies (50%, 45%, and 21% as measured during hospitalization). 14,18,29 In addition, other authors have reported that, of the minority of opioid-dependent women who elected to breastfeed, more than half stopped within 1 week, whereas a much larger percentage of the women in this case series elected to breastfeed until at least their 6-to 8-week follow-up visit.…”
Section: Discussionmentioning
confidence: 99%
“…(99) The American Academy of Pediatrics recommends breastfeeding for women taking methadone or buprenorphine, regardless of maternal dose as very little methadone (1–3% of the maternal weigh-adjusted dose) and minimal buprenorphine (<1% of the maternal weight-adjusted dose) is present in breastmilk. (99101, 106108)…”
Section: Postpartum Carementioning
confidence: 99%
“…57 Infant exposure appears to be up to 2.4% of the maternal weight-adjusted dose. 55,56,58 However, buprenorphine can be abused, and although the significance in humans is unknown, labeling for buprenorphine and buprenorphine/naloxone combinations states that use is not advised by lactating women, because animal lactation studies have shown decreased milk production and viability of the offspring. FDA labeling also advises caution for use of naltrexone in nursing infants of opioiddependent women.…”
Section: Drugs For Smoking Cessation or To Treat Substance Abuse/ Alcmentioning
confidence: 99%